Creativity as a resource for managing opportunities - Viktorova, V. S. (ТДАТУ, 2020)
The purpose of this article is to consider a set of theoretical aspects that relate to creative thinking, its barriers and ways of development. Among the famous scientists who have studied the problems of creativity, Thorpe Scott and Rod Judkins should be distinguished.
Keywords: creativity; flexibility in the management; development of creative thinking